Socio-Emotional Accompaniment in Pandemic: PACE Tutoring for Fourth Year High School Students - Vásquez-Villegas, Milena (Revista Saberes Educativos, 2021)
Socioemotional accompaniment is one of the areas identified by UNESCO as fundamental to be developed in the educational field, in the context of the COVID-19 pandemic during 2020. The Personal Management Area of the Support and Effective Access to Higher Education Program (PACE) of the Universidad Austral of Chile (UACh), Puerto Montt, has as its main objective to address the socioemotional and vocational development of students in their preparatory stage for university. This article presents the methodological strategies for the implementation of actions that allowed the Personal Management Area of PACE-UACh to comply with the guidelines proposed by the Ministry of Education, for 4th year high school students in a virtual context. Among the main findings is the contribution for decision-making, expansion of expectations and construction of life projects, as well as for the identification of talents and the process of self-knowledge of the students. Finally, the importance of accompanying socioemotional development is highlighted as an ethical duty and an adequate connectivity is indicated as a fundamental right that should be guaranteed, in order to meet the educational needs of the population in the context of a health emergency.